KOMUNIKASI TERAPEUTIK PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR JAMBI - Faridah Faridah; Iin Indrawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Communication is a basic element of human interaction that allows one to establish, maintain and improve contracts with others because communication is done by someone, every day people often mistakenly think that communication is easy. But actually it is a complex process that involves behavior and relationships and allows individuals to associate with others and with their surroundings.As an effort to improve elderly health, it is necessary to continuously provide information to scientists, both individuals and groups so that the elderly can change from not knowing to knowing that the elderly can live healthy and productive lives, but with limited physical, psychological and mental needs approaches and methods so that messages are delivered more effectively.The method carried out on the elderly in providing information about the Healthy Lifestyle for the Elderly and the importance of eating fruit and vegetables through the approach of